ANTIOXIDANT POTENTIAL OF CHERRY STALK EXTRACTS - PRVULOVIĆ, Dejan; KOLAROV, Radenka; LJUBOJEVIĆ, Mirjana; BARAĆ, Goran; PEIĆ TUKULJAC, Marijana (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Cherry stalks, as primary by-products of sour cherry (Prunus cerasus L.) and sweet cherry (Prunus avium L.) harvesting, are often considered agricultural and industrial waste. However, cherry stalks are recognized in traditional and ethno medicine for their therapeutic properties, due to their high content of natural antioxidants. In this study, the concentrations of total phenolic and total flavonoid compounds, as well as antioxidant activity, were evaluated in different cherry stalk extracts (aqueous, methanol, ethanol, and acetone) obtained from sweet cherry cultivars, sour cherry cultivars, and a wild cherry sample. The results depended on the cultivar and the solvent used for extraction. The highest concentrations of total phenolic and total flavonoid compounds were observed in acetone extracts. In various antioxidant tests, the antioxidant activity varied depending on the genotype.